MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA DENGAN MENERAPKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THE POWER OF TWO - Indah Annisa (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding of  mathematical concepts  is  one  of  the  learning  objectives and  basic  skills  that  must  be  develoved optimally. But in fact students’s understanding of mathematical concepts is not optimal, it is also found in class VIII of SMPN 4  Padang. One of factors that cause  this  learning  is  not  centered on students. Efforts to improve students’s understanding of mathematical concepts is using cooperative learning model the power of two. Type of research  is  quasi experimental  with   static   group   design.   Purpose  of  research   is   to   know   whether   students’s understanding of mathematical concepts who use cooperative learning model the power of two is better than conventional learning  is class VIII of SMPN 4  Padang.  Result  of research show that  indicate that  students’s understanding mathematical concepts who use cooperative learning model the power of two is better than conventional learning is class VIII of SMPN 4 Padang. Keyword – cooperative learning model the power of two, conventional learning, understanding of mathematical concepts, conventional learning.